PENGARUH KONSENTRASI GARAM TERHADAP KADAR HCN DAN PENILAIAN SENSORI PIKEL REBUNG - Rika Saskia; Usman Pato; Rahmayuni Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Pikel is the result of processing vegetable material with the addition of salt and preserved in acid with or without the addition of sugars and spices to flavor.The purpose of this study was to determine the effect of the concentration of salts in the fermentation of pickled bamboo shoots, and to get a proper salt concentration on the quality of the resulting pickle. This study was carried out experimentally using a completely randomized design (CRD) with 5 treatments and 3 replications. The treatment in this study is the concentration of salt solution consisting of G1 (salt solution 2%), G2 (salt solution 4%), G3 (salt solution 6%), G4 (salt solution 8%) and G5 (salt solution 10% ). Parameters measured were HCN content and sensory assessment test descriptive and hedonic test on color, texture and aroma. The results showed that variations in salt concentrations affect all parameters observed. The best treatment is the treatment of G4 with a concentration of 8% saline solution with HCN levels of 49.99 mg / 100 g, the sensory descriptive test ratings on pickel shoots against a whitey color, the texture rather hard, rather flavorful acid  and hedonic test  on colors was like, teskstur was like, somewhat like aroma and overall ratings assess was like. Keywords :Fermented, pickle, bamboo shoots